1998
DOI: 10.1023/a:1008817812520
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although quality of life evaluations are widely used throughout medicine, relatively little is known about the psychological processes involved in making these judgements. What is known is that quality of life judgements are not straightforwardly associated with objective measures of health status or clinician ratings. In particular, patient affect appears to be associated with quality of life ratings but whether this relationship is secondary to physical health or not is controversial. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…It has been suggested that the proportion of cases, for example, on the HADS having a DSM-1V-R diagnosis of general anxiety is poor. 10 One of the purposes, of the present study was to identify possible cases of general anxiety rather than diagnose generalised anxiety disorder, and the results concur with previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that the proportion of cases, for example, on the HADS having a DSM-1V-R diagnosis of general anxiety is poor. 10 One of the purposes, of the present study was to identify possible cases of general anxiety rather than diagnose generalised anxiety disorder, and the results concur with previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…The four studies that used more extensive versions of the Short Form Health Survey (SF-20 to SF-36) allowed a comparison based on the subscales of the Short Form; physical function, role function, overall health, social function, pain and mental health [12, 15, 16, 18]. This comparison shows that depressive symptoms were most strongly associated with role function and social function (moderate to severely poorer scores, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with both diabetes and depressive symptoms were less satisfied with their treatment, experienced a greater impact of the treatment, worried more about the impact of diabetes in the future and about the social and vocational impact of diabetes. In addition to these studies, Kohen et al [15] investigated the association of depressive symptoms with the number of hypoglycaemic events and other symptoms of diabetes, but did not find any difference between diabetic individuals with and without depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…1). Sixty-five primary studies (69 publications) fulfilled inclusion criteria (diabetes: n = 23 [10,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]; CAD: n = 26 [57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83]; asthma: n = 13 [84,85,86,87,88,89,90,91,92,93,94,95,96,97]; chronic back pain: n = 3 [98,99,100]; colorectal cancer: n = 0). In most cases, depressive disorders were studied (n = 45), followed by anxiety disorders (n = 14), any mental disorder (i.e.…”
Section: Resultsmentioning
confidence: 99%